A New Hyperbolic Variation Method for Settlement Analysis of Axially Loaded Single Friction Piles - Mert, Mustafa; Özkan, Mustafa Tuğrul (Springer, 2020)
This study describes a new hyperbolic method based on load transfer method for settlement analysis of axially loaded single friction piles. The new method is obtained by examining 14 pile load tests. The examined test piles were loaded until the piles were failed, and they were chosen from friction piles having variable diameters from 0.6 to 2.0 m and located in different geographical regions. Twelve of these test piles were circular bored piles, and two of them were barrette piles. According to the proposed hyperbolic method, the load–settlement graph is divided into two parts, and the relationship between load and settlement is defined by using two different hyperbolic variations each corresponding to one of the parts. Results of the settlement analysis of the four test piles obtained from the new proposed method and the four from the different methods based on load transfer method are presented comparatively with each other and with the pile load test results. The results of the pile settlement analysis and those of the pile load tests demonstrate that the new hyperbolic method yields accurate results for the most bored friction piles. The load settlement plots obtained by the new method match appropriately with measured values. On the other hand, the results of the barrette piles obtained from the hyperbolic method do not show the proper fit like those of the bored piles, when they are compared to those of the other methods based on the load transfer method.
Keywords: Pile; Settlement; Failure; Load Transfer Method; Instrumentation and Monitoring